Potential Application of Probiotics in the Prevention and Treatment of Inflammatory Bowel Diseases - del Carmen, Silvina Andrea (2011)
Lactic acid bacteria (LAB) represent a heterogeneous group of microorganisms that are naturally present in many foods and possess a wide range of therapeutic properties. The aim of this paper is to present an overview of the current expanding knowledge of the mechanisms by which LAB and other probiotic microorganisms participate in the prevention and treatment of inflammatory bowel diseases. These include changes in the gut microbiota, stimulation of the host immune responses, and reduction of the oxidative stress due to their antioxidant properties. A brief overview of the uses of genetically engineered LAB that produce either antioxidant enzymes (such as catalase and superoxide dismutase) or anti-inflammatory cytokines (such as IL-10) will also be discussed. This paper will show that probiotics should be considered in treatment protocols of IBD since they provide many beneficial effects and can enhance the effectiveness of traditional used medicines.